Profil kesalahan dalam menyelesaikan soal cerita materi pecahan - Maya Novita Sari; Riyadi Riyadi; Siti Kamsiyati (Universitas Sebelas Maret, 2021)
This research purpose to analtyze the errors carried out by student based on prosedural analysis Newman Error Analysis ini solving fraction material story questions. Newman’s analysis stresses on five spresific activity, which were reading, comprehension, transformation, process skill, and encoding. This research used qualitative with a sigle instrument. The subjects of this research were 5th grade students form SD Negeri Kawatan No 19 Surakarta academic year 2020/. The research subjects were taken purpoisvely with the consideration of predetermined criteria. The validity test technique used source triangulation and ted tehcnical triangulation. Validity test technique used source triangulation and tehnical triangulation. In the research used data analysis technique the domain analysis model and interactive analysis according to Miles and Huberman.The result of this research showed the percentage from the most errors to the smallest error made by students in solving fraction material story questions, namely writing errors questions, encoding error 100% of the answers followed by process skills error 91,66% and transformation errors 37,5%.The existence of this error analysis can help teachers to correct existing error apply more caried ethod in accordance with subsequent mathematics leraning.